Optically Active P-5-Deltacyclenes: A Unique Cage-Inversion Reaction and Some Transition-Metal Complexes of the Rearranged Cage - Höhn, Christine; Bauer, Walter; Heinemann, Frank Wilhelm; Torrell, Sergi Huguet; Keller, Irene; Rohwer, Lars; Shubina, Tatyana; Zenneck, Ulrich (European Journal of Inorganic Chemistry, 2016)
Cage-chiral P-5-deltacyclene 1 is available as a pair of highly enriched P-C cage enantiomers 1' and 1 '', which exist as pairs of epimers a and b. Deprotonation of cage atom P1 initiates a rearrangement reaction, in which P1 and the neighboring carbon atom C4, together with its substituent, change places to form optically active iso-P-5-deltacyclene enantiomers 6 '' and 6', again as pairs of epimers. The CD spectra of related pairs of optically active cages 1 and 6 consist of almost mirror-symmetric curves, an indicator of mirror-symmetric cage structures. This surprising result was verified by an absolute structure determination of the W(CO)(5) complex 9a ''. With the exception of the two cage nuclei that had changed places in relation to starting material 1', all other cage nuclei of rearrangement product 6a '' occupy mirror-symmetric positions. To the best of our knowledge, this represents the first cage-inversion reaction of an optically active compound. P1 is the only active donor center of 6 involved in the bonding of M(CO)(5) fragments (M = Cr, Mo, W). The chiroptical properties of Cr(CO)(5) complex 7a' and W(CO)(5) complex 9a '' are almost mirror-symmetric and resemble those of the free cages 6' and 6 '', respectively. The coordinated transition-metal complex fragments do not contribute significantly to the Cotton effects of the P-C cage. A DFT analysis of the deprotonated cage anions [1 - H](-) and [6 - H](-) predicts a driving force of -20.3 kcal mol(-1) for the rearrangement reaction.
Keywords: Cage compounds; Cage inversion; Coordination compounds; Chirality; Circular dichroism